The quality of higher education in Colombia: some strategic evasion practices (Praxis Educativa, 2020)
In Colombia, some universities, under the hard and bloody struggle not to disappear, and which I have called "pseudo emerging", for their "no-power-more power", have incorporated strategic practices into their repertoire of evasion to look at, not only to obtaining quality certification, but also to the acquisition of income and profit: camouflage, yeast effect, mimesis and hyperactivity. These four evasion practices are not given continuously or established in a hierarchical order. Rather, they juxtapose each other until they form a crammed network of information and data where utility becomes an educational measure.
Keywords: quality; camouflage; yeast; mimesis; hyperactivity.